Subarachnoid haemorrhage in pregnancy after fertilisation with egg donation: a case report and review of the literature - Noemi J. Hughes; Saeed M.S.R. Choudhury; Sidath H. Liyanage; Munawar Hussain (SAGE Publishing, 2021)
We report a rare case of in vitro fertilisation (IVF) with egg donation complicated by a subarachnoid haemorrhage (SAH). Haemostatic changes related to IVF are known to increase risk of venous thrombosis; however, less is known regarding the risk of arterial events such as cerebrovascular accidents (CVA). Matrix metalloprotease-9 (MMP-9) upregulated in IVF patients may have a role in arterial aneurysm formation, which is the most common cause of SAH. Further research is required to assess the benefit of screening for risk of CVA and the best way to manage this in the IVF population. This may have implications for the ethics of offering certain procedures such as egg donation to women with pre-existing risk factors.